Parvovirus b19 DNA CpG dinucleotide methylation and epigenetic regulation of viral expression. - Francesca Bonvicini (Public Library of Science (PLoS), 2012)
CpG DNA methylation is one of the main epigenetic modifications playing a role in the control of gene expression. For DNA viruses whose genome has the ability to integrate in the host genome or to maintain as a latent episome, a correlation has been found between the extent of DNA methylation and viral quiescence. No information is available for Parvovirus B19, a human pathogenic virus, which is capable of both lytic and persistent infections. Within Parvovirus B19 genome, the inverted terminal regions display all the characteristic signatures of a genomic CpG island; therefore we hypothesised a role of CpG dinucleotide methylation in the regulation of viral genome expression.The analysis of CpG dinucleotide methylation of Parvovirus B19 DNA was carried out by an aptly designed quantitative real-time PCR assay on bisulfite-modified DNA. The effects of CpG methylation on the regulation of viral genome expression were first investigated by transfection of either unmethylated or in vitro methylated viral DNA in a model cell line, showing that methylation of viral DNA was correlated to lower expression levels of the viral genome. Then, in the course of in vitro infections in different cellular environments, it was observed that absence of viral expression and genome replication were both correlated to increasing levels of CpG methylation of viral DNA. Finally, the presence of CpG methylation was documented in viral DNA present in bioptic samples, indicating the occurrence and a possible role of this epigenetic modification in the course of natural infections.The presence of an epigenetic level of regulation of viral genome expression, possibly correlated to the silencing of the viral genome and contributing to the maintenance of the virus in tissues, can be relevant to the balance and outcome of the different types of infection associated to Parvovirus B19.